2000
DOI: 10.1007/s004019900172
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of microglial activation after human traumatic brain injury are revealed by delayed expression of macrophage-related proteins MRP8 and MRP14

Abstract: Human traumatic brain injury (TBI) is ideally suited for investigation of the kinetics of human microglial cell activation as the onset of lesion formation is precisely defined. The present study provides evidence of a distinct delay in macrophage/microglia response following TBI. Eighteen brains of patients who had survived TBI for 1 h to 6 months were analysed by immunohistology. Samples of contusional and non-contusional areas were studied using antibodies directed against antigens of microglia/ macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 52 publications
9
70
2
1
Order By: Relevance
“…Studies in humans with TBI have revealed a striking delay of microglial activation and proliferation. Markers of microglial activation and proliferation were not detected until 3 days post TBI (Beschorner et al, 2000;Engel et al, 2000) whereas the same markers were expressed early in cerebral ischemia (Postler et al, 1997). This observation although in line with some findings in experimental models (Aihara et al, 1995;Holmin et al, 1997) cannot be fully understood.…”
Section: Innate Immunitysupporting
confidence: 60%
“…Studies in humans with TBI have revealed a striking delay of microglial activation and proliferation. Markers of microglial activation and proliferation were not detected until 3 days post TBI (Beschorner et al, 2000;Engel et al, 2000) whereas the same markers were expressed early in cerebral ischemia (Postler et al, 1997). This observation although in line with some findings in experimental models (Aihara et al, 1995;Holmin et al, 1997) cannot be fully understood.…”
Section: Innate Immunitysupporting
confidence: 60%
“…However, with lesion progression, the clear demarcation may fade, rendering an unequivocal identification more difficult. Other distinctions have been made by superoxide dismutase expression (250), whereas expression of the calcium binding macrophage related proteins MRP8/S100A8 and MRP-14/S100A9 is thought to identify circulating and more recently invaded monocytes/macrophages (375,490), while delayed expression in microglia can occur as well (249).…”
Section: B Identificationmentioning
confidence: 99%
“…38 Cerebral ischemia, traumatic brain injury, and Alzheimer's disease (AD) have been reported to be associated with altered expression/function of S100 family members. 22,39,40,41 Recently, S100a9 was found to be increased within neuritic plaques and reactive glia, thus suggesting a role in the inflammatory component of AD pathogenesis. 22 Furthermore, inhibition of S100a9 may be a possible therapeutic target for AD.…”
Section: Discussionmentioning
confidence: 99%